Masculinity Reconstruction by K-Pop Idol BTS: BTS ARMY’S Reception Analysis Towards BTS’s Musics and Contents - Perwiradmoko, Jasmine Qurrota Ayuni (UI Scholars Hub, 2023)
This study have an aim to see the reception analysis from BTS ARMY towards the reconstruction of masculinity that BTS do. The previous studies showed that the K-Pop Male Idol have reconstructed the meaning of masculinity, and also see how the masculinity reconstruction that the K-Pop Male Idol did has been consumed by the fangirls. However, those studies have not explained about how the fangirls point of view about the reconstruction of masculinity, especially if it is contexted in Indonesia’s masculinity construction. This study argues that the various product of Korean popular culture or Hallyu, which in the context of this research is BTS’s musics and content that is spread through a lot of digital media, that shows masculinity construction which different from the hegemonic masculinity construction in Indonesian society, which in the end is able to make BTS ARMY negotiate the meaning of the masculinity that is different from their society’s hegemonic masculinity. The research method is a qualitative approach by conducting a reception analysis to the BTS content by conducting an indepth interviews to BTS ARMY related to the BTS masculinity image that is delivered through the content that they produced. The findings found that, BTS showing a reconstruction of masculinity by breaking the norms which in all this time exist in the hegemonic masculinity, through their musics and contents which was spread through various digital media. So by through it, the informant ARMY precisely gain a new comprehension about masculinity concept which is different than the hegemonic masculinity that exists in their society.